Psychological effects and associated factors among vaccinated and unvaccinated general population against COVID-19 infection in Bangladesh - Alam, Md. Dhedharul; Abedin, Md. Joynal; Islam, Asraful; Mosfeq-Ul-Hasan, Md.; Rahman, Obaydur; Xu, Yi (Frontiers in Psychiatry, 2022)
Background: The global effort to develop herd immunity in the general public against the COVID-19 pandemic is currently ongoing. However, there have been no studies on how the COVID-19 vaccine affects mental health in the context of the COVID-19 pandemic in Bangladesh. The present study investigated the psychological effects and associated factors among vaccinated and unvaccinated general populations against COVID-19 infection in Bangladesh. Methods: A nationwide online cross-sectional survey was conducted in Bangladesh from June 23 to December 25, 2021. The frequency of symptoms of psychological distress, depression, anxiety, stress, post-traumatic stress disorder (PTSD), insomnia, and fear was assessed using the Bangla versions of the GHQ-12, PHQ-2, GAD-2, PSS-4, PC-PTSD-5, ISI, and FCV-19S scales, respectively. Results: A total of 3,013 people were gathered from all eight divisions of Bangladesh, with 1,272 (42.2%) being vaccinated and 1,741 (57.8%) being unvaccinated. Compared with unvaccinated populations, vaccinated populations had a significantly lower prevalence rates of psychological distress (36.4 vs. 51.5%), depression (21.1 vs. 37.9%), anxiety (25.1 vs. 44.9%), stress (19.4 vs. 30.4%), PTSD (29.4 vs. 38.3%), insomnia (18.7 vs. 39.4%), and fear symptoms (16.1 vs. 27.5%). Among vaccinated populations, males were significantly associated with a higher risk of symptoms of depression, anxiety, and PTSD. Respondents who lived in nuclear families were a significantly higher chance of experiencing psychological distress, depression, anxiety, and fear symptoms. Respondents who lost family members, friends, or colleagues due to the COVID-19 pandemic had a significantly higher chance of experiencing symptoms of psychological distress, anxiety, and PTSD. On the other hand, unvaccinated populations who lived in the Dhaka division were significantly associated with an increased risk of depression, anxiety, stress, and insomnia symptoms. Except for PTSD and fear symptoms, unemployed participants had considerably higher rates of psychological distress, depression, anxiety, stress, and insomnia symptoms. Respondents who had poor social support had a significantly greater experience of depression, anxiety, and PTSD symptoms. Conclusions: This study recommends emphasizing the vaccinated to unvaccinated populations as soon as possible to control the infection and improve psychological effects. They also required special care, health-related education, and psychological assistance.